Welding investigation on AA6063-T6 aluminium alloy during friction stir welding process - Aditya Mamgain; Ajay Pratap Singh; Vivek Singh (Penerbit Universiti Kebangsaan Malaysia, 2023)
The Friction stir welding (FSW) is widely used to weld aluminium alloy for industrial applications such as shipbuilding, aerospace and automobile due to its lighter weight and high strength. The current work is carried out to examine the different process parameters to weld AA6063-T6 aluminum alloy with FSW process. The tool rotation speed, feed, plunging depth and dwell time are considered as the welding parameter. The three test coupons have been welded at three different rotational speeds. The tensile strength and hardness at the weld vary with the speed of rotation of the tool. The higher tensile strength is achieved at lower tool rotational speed. The tensile strength achieved at 1000rpm and 1400rpm is 191Mpa and 131rpm respectively. The higher strength is achieved due to the refinement of grains and recrystallization in stirred zone. The microstructure test confirms the presence of uniformly fine grains at weld area and equiaxed grains at HAZ region.